Evaluating the effectiveness of handheld ultrasound in primary blast lung injury: a comprehensive study - Shifeng Shao; Zhengbin Wu; Jun Liu; Zhikang Liao; Yuan Yao; Liang Zhang; Yaoli Wang; Hui Zhao (Scientific Reports)
Abstract The incidence of blast injuries has been rising globally, particularly affecting the lungs due to their vulnerability. Primary blast lung injury (PBLI) is associated with high morbidity and mortality rates, while early diagnostic methods are limited. With advancements in medical technology, and portable handheld ultrasound devices, the efficacy of ultrasound in detecting occult lung injuries early remains unclear. This study evaluates the effectiveness of immediate lung ultrasound in diagnosing PBLI. The study involved 25 healthy male Bama mini-pigs subjected to BST-I-type biological shock wave tubes. The pigs were randomly assigned to non-injured and injured groups with driving pressures of 4.0 MPa, 4.5 MPa, and 4.8 MPa. Four PBLI models were created: no injury, minor, moderate, serious and severe. Immediate lung ultrasound following the BLUE-PLUS protocol and arterial blood gas analysis were conducted pre-injury and 0.5 h, 3 h, 6 h, 12 h, and 24 h post-injury, respectively. The study analyzed lung ultrasound score differences and their correlations with lung function parameters, using ROC analysis to determine early diagnostic standards and mortality prediction efficacy. The study found that in cases of moderate and severe PBLI, lung ultrasound scores and AaDO2 significantly increased at 0.5 h post-injury, while PaO2 decreased. There was good consistency between left and right lung ultrasound results at all times. Lung ultrasound scores were significantly correlated with PaO2 and AaDO2 but not with PaCO2. The scores accurately predicted injury severity at various time points within 24 h post-injury, and the 0.5 h lung ultrasound score predicted 24 h mortality with 95.8% efficiency. PBLI exhibits hidden severity, necessitating improved early diagnostics. Immediate lung ultrasound provides effective differentiation for moderate and severe PBLI at multiple time points within 24 h post-injury, is easy to implement, and offers effective mortality risk prediction as early as 0.5 h post-injury. These findings underscore lung ultrasound’s significant clinical application value in pre-hospital early treatment settings for PBLI.